Membrane-disruptive engineered peptide amphiphiles restrain the proliferation of penicillins and cephalosporins resistant Vibrio alginolyticus and Vibrio parahaemolyticus in instant jellyfish. (May 2022) - Zeng, Ping; Cheng, Qipeng; Xu, Jiangtao; Xu, Qi; Xu, Yating; Gao, Wei; Wong, Kwok-Yin; Chan, Kin-Fai; Chen, Sheng; Yi, Lanhua
Abstract: Over 1 billion people rely on seafood as their primary source of protein and Vibrio spp. is the most important pathogen of foodborne disease outbreak related to consumption of seafood. Moreover, the rise of drug-resistant Vibrio strains further increases the difficulty of clinical treatment. However, there is no food preservative available to combat drug-resistant Vibrio spp. in seafood. In this study, we designed and synthesized three novel antibacterial peptides (ABPs) derived from zp3 (GIIAGIIIKIKK-NH2 ). One of them, 3 K 5 K 7 G (GIKAKIGIKIKK-NH2 ), had bioactivity against all tested penicillins and cephalosporins resistant Vibrio with minimal inhibitory concentration (MIC) values at 2–16 μM, performing better than its template zp3 . 3 K 5 K 7 G demonstrated favourable antibacterial capability in instant jellyfish, killing more than 99% Vibrio alginolyticus cells after 64 μM treatment for 4 h. Peptide 3 K 5 K 7 G could disrupt the cell membrane, resulting in rapid membrane potential dissipation. Next, this molecule could penetrate inside cytoplasm and further bind with DNA. Importantly, 3 K 5 K 7 G showed low cytotoxicity to mammalian cells (95% Vero cells survived in the presence of 160 μM 3 K 5 K 7 G ). Collectively, 3 K 5 K 7 G has the potential to be developed into a promising food-grade antibacterial additive, especially against those resistant Vibrio spp. in seafood. Highlights: 3 K 5 K 7 G performed better antibacterial activity than its template zp3 with α-helix structure. 3 K 5 K 7 G had MIC values at 2–16 μM to penicillins and cephalosporins resistant Vibrio. 3 K 5 K 7 G killed more than 99% V. alginolyticus in instant jellyfish after 4 h treatment. 3 K 5 K 7 G disrupted the cell membrane, resulting in rapid membrane potential dissipation. 3 K 5 K 7 G had low cytotoxicity to mammalian cells.